Synthesis and spectroscopic studies of Arylethynylsilanes - Shao, Guang; Gleiter, Rolf (Chemistry, 2007)
A variety of arylethynylsilanes (Ar-CCC6H4CC)nSiMe4−n were prepared successfully by reaction of the corresponding chlorosilanes Me4−nSiCln with ArCCC6H4CCM (M=Li, MgBr), which was prepared by treatment of ethynyl(diarylethyne)s ArCCC6H4CCH with BuLi or MeMgBr. The ethynyl(diarylethyne)s were readily prepared in good yields by the double-elimination method: addition of lithium hexamethyldisilazide to a mixture of ArCH2SO2Ph, TMSCCC6H4CHO, and ClP(O)(OEt)2, followed by desilylation. In the tetrakis(arylethynyl)silanes (ArCCC6H4CC)4Si thus prepared, through-space conjugation of four triple bonds on the silicon atom emerges as a result of participation of the silicon orbitals in the acetylenic π orbitals. This participation enhances the emissive quantum yields of arylethynylsilanes with an increase in the number of arylethynyl moieties on silicon: quantum yields of emission (ΦF) of 0.72 for (MeOC6H4CCC6H4CC)4Si, 0.53 for (MeOC6H4CCC6H4CC)2SiMe2, and 0.47 for MeO-C6H4CCC6H4CCSiMe3 were obtained. Although this enhancement effect was also observed in the phenylethynylarylsilane (MeOC6H4CCC6H4)2SiMe2, the bis(arylethynyl)disilane (MeOC6H4CCC6H4CC-SiMe2)2 exhibited non-enhanced emission.